Hadith #2382 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Aisha bint Abi Bakr; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Amr bin Maymun al-Aw'di عمرو بن ميمون الأودي أبو عبد الله; Ziyad bin 'Alaqa زياد بن علاقة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to kiss and embrace while he was fasting, but he was the one of you who had most control over his desire.
Grade: Sahih

Hadith #2523 - Sunan Abi Dawud - Abdullah bin Rabi'a bin Farqad عبد الله بن ربيعة بن فرقد السلمي; Amr bin Maymun al-Aw'di عمرو بن ميمون الأودي أبو عبد الله; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaid bin Khalid al-Slmy (Sunan Abi Dawud)
When Negus died, we were told that a light would be seen perpetually at his grave.
Grade: Hasan

Hadith #2558 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Amr bin Maymun al-Aw'di عمرو بن ميمون الأودي أبو عبد الله; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Mu'adh ibn Jabal (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited to ride a camel which eats dung.
Grade: Hasan Sahih